Improvement of knowledge, procedures and attitudes of students in Secondary Education after being exposed to an intervention in Physical Education for Health - J. Molina-García; I. Castillo; C. Pablos (Asociación Española de Ciencias del Deporte, 2010)
The purpose of this work was to analyse the psychological well-being and the sport practice in a sample of 121 university students (72 men and 49 women) with an average age of 20.46 years (± 2.58). The results show that men have a greater self-esteem and practise more sport than women. With regard to the relation between the practice of sport and the self-esteem there are not significant differences between who are active physically and who are not, as much in men as in women. In the same way, significant differences have not been found in the subjective vitality based on the sport practice. With respect to the relation between the satisfaction with the life and the practice of sport there are significant differences between the men who are physically active and the ones less active, but there are not significant differences between women. Key words: sport, psychological well-being, university student.